All set in stone? How essentialist beliefs about aging affect older workers' motivation to continue working beyond retirement age. (15th June 2022) - Weiss, Mona; Weiss, David; Zacher, Hannes
Summary: Although population aging requires that employees increasingly work beyond traditional retirement ages, negative age stereotypes often portray older workers as unwilling or unable to work longer. However, recent lifespan developmental research suggests that there are significant individual differences in how fixed versus malleable people perceive the aging process possibly affecting how they envision their occupational future. We develop and test a theoretical model on the role of essentialist beliefs about aging (i.e., the extent to which people believe that aging is an immutable, genetically determined process) in shaping occupational future time perspective and, in turn, motivation to continue working beyond retirement age. Specifically, we hypothesized that older workers (40–65 years) who more strongly endorse essentialist beliefs about aging will be less motivated to continue working beyond retirement age, because they have a more constrained occupational future time perspective. On the basis of a three‐wave study ( N = 617) and an experiment ( N = 358), we find evidence for our proposed indirect effect model, above and beyond previously established control variables (e.g., age, income, health, and age stereotypes). Our findings advance theorizing on work motivation in later adulthood and have important organizational implications in the context of demographic change.